ADHD and Intellectual Disability: using ADHD medication - K. Courtenay; B. Perera (European Psychiatry, 2022)
Introduction Mental disorders and ADHD in people with ID are higher than in the general population.Clinicians may be reluctant to diagnose ADHD in people with ID. They could be denied effective treatment.